1998
DOI: 10.1016/s0022-5347(01)63694-2
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Dietary Calcium and Other Nutrients in Idiopathic Renal Calcium Stone Formers With Low Bone Mineral Content

Abstract: A primary abnormality of bone metabolism could be a reasonable explanation of reduced bone density observed in renal stone formers on a low calcium diet since serum parathyroid hormone levels are in the normal range. From a therapeutic point of view these data confirm that restriction of dairy products in renal stone formers should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Thus, dietary restriction of calcium not only fails to decrease the incidence of kidney stones, but possibly further aggravates bone mineral loss. In fact, several investigators have shown that low-calcium diet in idiopathic hypercalciuria patients is associated with reduced BMD [21,24,28,44].…”
Section: Calcium Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, dietary restriction of calcium not only fails to decrease the incidence of kidney stones, but possibly further aggravates bone mineral loss. In fact, several investigators have shown that low-calcium diet in idiopathic hypercalciuria patients is associated with reduced BMD [21,24,28,44].…”
Section: Calcium Intakementioning
confidence: 99%
“…Similarly, some studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] have demonstrated that these patients have increased bone resorption markers (Table 1).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, none of the markers correlated with BMD z-score of the femoral neck or spine in a significant manner. Another study in 48 male calcium stone formers observed no significant differences in vertebral and hip BMD between hypercalciuric and normocalciuric stone formers [44]. However, hypercalciuric stone formers had significant increases in 2 h PYD excretion and in serum total alkaline phosphatase consistent with an increase in bone turnover.…”
Section: Clinical Studiesmentioning
confidence: 91%
“…Taylor and Curhan [13] cited the limited effectiveness against stone formation of a lowcalcium diet [34] and fear of bone loss from the dietary calcium restriction. In addition, the epidemiological and clinical studies discussed above [12,17,44] suggest that reduced calcium intake in stone formers may actually serve to perturb the bone loss. Our approach has been to employ calcium restriction only in hypercalciuric patients [87] in combination with a hypocalciuric agent and potassium citrate [88].…”
Section: Calciummentioning
confidence: 99%
“…Hypercalciuria is associated with important alterations in calcium-phosphate homeostasis [10], persistent overproduction of cytokines predisposing bone loss [11], parathormone (PTH), and calcitriol-mediated pathways [12]. Furthermore, as observed in some studies, subjects with nephrolithiasis may limit their dietary calcium intake, resulting in a negative calcium balance that predisposes the individual to a higher risk of bone loss over time [13,14].…”
Section: Introductionmentioning
confidence: 99%